Dental rehabilitation of adult patients with tooth loss and obstructive sleep apnea (literature review) - Doroshenko О. М.; Bida В. І.; Volosovets Т. М.; Omelianenko О. А.; Doroshenko М. В.; Bida О. О.; Andrusenko А. С.; Doroshenko М. М. (Actual Dentistry, 2024)
Introduction. Dental sleep medicine is a branch of dental practice that deals with the treatment of sleep-related breathing disorders, including obstructive sleep apnea (OSA) in adults and children. However, daily practice shows that other sleep disorders also concern dentistry, including orofacial pain associated with sleep, xerostomia, hypersalivation, gastroesophageal reflux disease, temporomandibular joint dysfunction, and bruxism. Purpose: on the basis of a thorough analysis of literary sources, to study the main methods of dental rehabilitation of adult patients with obstructive sleep apnea and to compare their effectiveness. Materials and methods. Information search and analysis of scientific sources using scientometric databases Web of Science, PubMed, Google Scholar over the past 15 years. Conclusion. The analysis of the literature data of recent years has shown the wide spread of dental pathology in patients with OSA and the need to develop and implement modern multidisciplinary approaches to the treatment of this contingent with the involvement of practicing dentists in health care practice.